Unveiling the impact of allulose on oral microbiota and biofilm formation via a cariogenic potential assessment platform - Han, Seunghun; Rajitha, Kuthirakkal; Park, Sungbin; Lim, Jaeeui; Jung, Hee-Young; Kim, Junghyun; Kim, Dongyeop (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe increased consumption of refined carbohydrates, particularly sucrose, has contributed to metabolic disorders and oral diseases such as dental caries by promoting dysbiotic biofilm formation and reducing microbial diversity. Allulose, a rare sugar with physicochemical properties similar to sucrose, has been suggested to offer metabolic health benefits; however, its impact on oral biofilm ecology remains unclear.MethodsWe evaluated the cariogenic potential of allulose using a multi-tiered in vitro platform consisting of single-species planktonic and biofilm models, a dual-species biofilm model involving Streptococcus mutans (pathogen) and Streptococcus oralis (commensal), and a saliva-derived microcosm biofilm model. Key virulence indicators, including bacterial growth, acid production, biofilm biomass, exopolysaccharide (EPS) synthesis, and microbial community composition, were quantitatively assessed.ResultsCompared to sucrose, glucose, and fructose, allulose supported reduced bacterial growth and acid production, showing a profile similar to non-fermentable sugar alcohols such as xylitol and erythritol. Biofilms developed under allulose conditions lacked the dense EPS-enmeshed microcolonies and dome-shaped architecture characteristic of sucrose-induced S. mutans-dominant biofilms. In the saliva-derived microcosm model, allulose-treated biofilms maintained higher microbial diversity and preserved health-compatible genera such as Neisseria, Haemophilus, Veillonella, and Granulicatella.DiscussionThese findings demonstrate that allulose supports lower bacterial virulence activity and minimal biofilm formation compared to common dietary sugars while preserving microbial diversity. This highlights its potential as a non-cariogenic sugar alternative with microbiome-conscious benefits and provides ecological insight into how allulose may modulate oral biofilm structure and function.